Maak iets: Kleur/Blik/Ding - de Duve, Thierry; Parret, Herman; Peeters, Jan; Ketelers, Inge (Ghent Sint-Lukas Beeldende Kunst, 2005)
This book documents the project of Thierry de Duve during the academical year 2004-2005 at Sint-Lucas Visual Arts Ghent. The working process as well as the results, conclusions, evaluations and several readings are published. This book is the third an last one in the series. It was arranged and typeset by Bas Rogiers and Julie Peeters following the design of Inge Ketelers of the former editions (see 2003 and 2004).
Contributions by Fiona Tan, Nadine Plateau, Marc De Kesel, Howard Caygill, Arne Depyudt, Julie Peeters, Bas Rogiers, Dorinda Bielen, Sofie De Ville, Els Van Gheluwe, Jef Cuypers, Marijke Verlinden, Mandy Meissner, Bianca Raes, Joke Van Wauwe, Ruth Viaene, Simon Devolder, Joris Kritis, Lies Van Hee, Johanna Van Parys, Sander Van Den Broucke, Jan Fack, Pieter Van Snick, Marijke Verkaart, Eveline Bouttens, Bert Vissers, Sarah Eechaut & Tine Guns. Supervision by Thierry de Duve, Lucas Devriendt, Wim Lambrecht & Herman Parret.
Tentoonstelling, Gent, Witte Zaal, 26 september tot 7 oktober 2005
Keywords: Fine art; Exhibition; Education; Ghent (Belgium)